Predictability of language death: Structural compatibility and language contact. (July 2017) - Ghafar Samar, Reza; Bhatia, Tej K.
Abstract: Thousands of the world's languages are said to be rapidly vanishing (Abrams and Strogatz, 2003), and the issue of language death has emerged as one of the most significant phenomena for linguistic study. Research on language loss and death has, however, focused mostly on European-related languages and historical cases have not attracted due attention (Mufwene, 2001, 2004). Moreover, of the many factors argued to be of importance in causing language death, to the best of our knowledge, little reference has been made to language-internal factors. This study explores the historical outcomes of contact between Arabic–Persian and Arabic–Egyptian languages to shed more light on language maintenance or death under contact situations. Providing evidence from languages in contact and analyzing data form Persian–Arabic bilinguals, we explore why Egyptian Coptic died but Persian survived after the invasion of Arabs, and bring up a tentative hypothesis that the surface structural compatibility of the two languages in contact may lead to drastic changes and the possible death of the less dominant and less prestigious language. Structural equivalence/congruence or lack thereof is also suggested as a constraint on the competition-selection process of Mufwene's (2002) feature pool hypothesis. Highlights: Focusing on the survival of Persian and death of Coptic after Arabic invasion. Presenting data from modern Persian and Arabic contact situations. Hypothesizing that Structural congruence of languages in contact may predict their possible death or survival.